Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1039/c2an36347j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical incorporation of hemin in a ZnO–PPy nanocomposite on a Pt electrode as NOx sensor

Abstract: An electrochemical NO(x) sensor was fabricated based on the incorporation of hemin on a ZnO-PPy nanocomposite modified Pt electrode. Scanning electron microscopy, energy dispersive X-ray analysis and cyclic voltammetry were used to confirm the successful stepwise assembly procedure for the sensor. The electrocatalytical behavior of the sensor was investigated by cyclic voltammetry. The hemin-ZnO-PPy-Pt electrode exhibited characteristic hemin reversible redox peaks at 0.035 V and -0.11 V vs. Ag/AgCl respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that hybrid materials are highly suitable in sensing applications, showing enhanced sensor stability, sensitivity and selectivity. The inorganic phase can be diverse, ranging from metal oxides, metal nanoparticles, carbon nanotubes and graphene . Their incorporation into conducting polymers can increase the concentration of interacting sites with the analytes, improve the intra‐ and inter‐chain mobility of charge carriers in the polymer chains or even modify the affinity of the composite to the electron‐donor or ‐acceptor molecules .…”
Section: Materials For Gas Sensing21single‐element Materialsmentioning
confidence: 99%
“…Previous studies have demonstrated that hybrid materials are highly suitable in sensing applications, showing enhanced sensor stability, sensitivity and selectivity. The inorganic phase can be diverse, ranging from metal oxides, metal nanoparticles, carbon nanotubes and graphene . Their incorporation into conducting polymers can increase the concentration of interacting sites with the analytes, improve the intra‐ and inter‐chain mobility of charge carriers in the polymer chains or even modify the affinity of the composite to the electron‐donor or ‐acceptor molecules .…”
Section: Materials For Gas Sensing21single‐element Materialsmentioning
confidence: 99%
“…Kaushik et al 52 and Prakash et al 172 used WO 3 −PANI and hemin/ZnO-PPy nanocomposite thin film sensors, respectively, to detect NO x gases. The NO x gas sensing characteristics of the PPy-ZnO nanocomposites showed superior selectivity and reversibility to NO x compared to PPy.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…The combinations of macrocycles, polymers, carbonaceous materials and inorganic materials are infinite, in particular if we combine more than two of them. As an example, we can cite the case of an electrochemical sensor in which hemin, an iron porphyrin complex, deposited on the surface of a Pt/ZnO/PPy structure, acts as an electrocatalyst to detect NOx at the sub micromolar level in aqueous solution [86]. Another example is that of CNT/PPy chemiresistors in which the polymer bears calix [4]arenes that ensure the selective recognition of aromatic VOCs like BTX [87].…”
Section: Challenges In Hybrid Materials-based Gas Sensingmentioning
confidence: 99%